Robert A. Dahl dan Studi tentang Fenomena Demokrasi di India - HARAHAP, HUSNUL ISA (Politeia: Jurnal Ilmu Politik, 2010)
How can explain the phenomena of Indian democracy? This study intends to answer this ques-tion. To have the use of Robert A. Dahl views and all at once criticize his views, this study also tries to explain about the secret of Indian democracy succeeded. The point is India is the po-verty country and there are no one of poverty country in the world have democracy for long time. Obvious have found that democracy in India has a lot of problem. And there are indica-tions about premise of problem Indian democracy as impact of economic variable. Mainly be-cause Indian democracies prevalent exist adjoin with human right violation, poverty, and âjatiâ (the system of caste). Apiece as the abnormal fact because there are exactly âreinforceâ de-mocracy in India. Hence, in this study the term of âpermissive democracyâ used to describe the uniqueness of Indian democracy condition. As implication of the theories, this study argue that clarification about the phenomena of democracy at poverty state need special concept as a dif-fering with developed countries because however there are difficulty to meaningful about de-mocracy without economic welfares. Absolutely, democracy cannot sufficient and cannot sur-vive without economic welfares.Keywords: democracy, permissive democracy, economic walfares.